Switching Between LC-ESI-MS/MS and EMIT Methods for Routine TDM of Valproic Acid in Pediatric Patients With Epilepsy: What Clinicians and Researchers Need to Know - Xia, Ying; Long, Jia-Yi; Shen, Meng-Yuan; Dong, Na; Guo, Hong-Li; Hu, Ya-Hui; Lu, Xiao-Peng; Ding, Xuan-Sheng; Chen, Feng; Qiu, Jin-Chun (Frontiers in Pharmacology, 2021)
Background: Valproic acid (VPA) is a widely used antiseizure medication and its dosing needs to be tailored individually through therapeutic drug monitoring (TDM) to avoid or prevent toxicity. Currently, immune-enzymatic assays such as Enzyme Multiplied Immunoassay Technique (EMIT), and Liquid Chromatography (LC)-based techniques, particularly coupled to Electrospray Ionization Tandem Mass Spectrometry (LC–ESI-MS/MS), resulting a potential lack of concordance between laboratories. Methods: In this study, plasma VPA concentrations were determined for 711 pediatric patients with epilepsy by a routine EMIT assay and by a validated in-house LC-ESI-MS/MS method on the same group of samples, aimed to address the aforementioned concern. Consistency between two assays was evaluated using linear regression and Bland-Altman analysis. Results: The calibration curve was linear in the range of 5.00–300 μg/ml for LC-ESI-MS/MS method and 1.00–150 μg/ml for EMIT assay, respectively. The two methods were proven to be accurate with quality control samples. As a result, a significant correlation between two methods was obtained with a regression equation described as [EMIT]=1.214×[LC−ESI−MS/MS]+3.054 (r2 = 0.9281). Bland-Altman plot showed a mean bias of 14.5 μg/ml (95% confidence interval (CI) (−0.2, 29.2) and a mean increase of 27.8% (95% CI (3.3, 52.4) measured by EMIT assay more than that measured by LC-ESI-MS/MS method. Conclusion: In conclusion, two methods were closely correlated, but EMIT assay overestimate VPA levels in human plasma compared with LC-ESI-MS/MS method. Due to the observed significant discordance between the tested methods, switching from immunoassays to LC-based techniques for TDM of VPA deserves close attention and therapeutic range of 35.0–75.0 μg/ml may be feasible. However, further studies are needed to evaluate the eligibility of this alternative range in the clinical practice. Clinicians should be informed when switching the VPA quantitation methods during the clinical practice.